Differential trends in cigarette smoking in the USA: is menthol slowing progress?. Issue 1 (30th August 2013) - Giovino, Gary A; Villanti, Andrea C; Mowery, Paul D; Sevilimedu, Varadan; Niaura, Raymond S; Vallone, Donna M; Abrams, David B
Abstract : Introduction: Mentholated cigarettes are at least as dangerous to an individual's health as non-mentholated varieties. The addition of menthol to cigarettes reduces perceived harshness of smoke, which can facilitate initiation. Here, we examine correlates of menthol use, national trends in smoking menthol and non-menthol cigarettes, and brand preferences over time. Methods: We estimated menthol cigarette use during 2004–2010 using annual data on persons ≥12 years old from the National Surveys on Drug Use and Health. We adjusted self-reported menthol status for selected brands that were either exclusively menthol or non-menthol, based on sales data. Data were weighted to provide national estimates. Results: Among cigarette smokers, menthol cigarette use was more common among 12–17 year olds (56.7%) and 18–25 year olds (45.0%) than among older persons (range 30.5% to 34.7%). In a multivariable analysis, menthol use was associated with being younger, female and of non-Caucasian race/ethnicity. Among all adolescents, the percentage who smoked non-menthol cigarettes decreased from 2004–2010, while menthol smoking rates remained constant; among all young adults, the percentage who smoked non-menthol cigarettes also declined, while menthol smoking rates increased. The use of Camel menthol and Marlboro menthol increased among adolescent and young adult smokers, particularly non-Hispanic Caucasians, during the study period. Conclusions: Young people are heavy consumers of mentholated cigarettes. Progress in reducing youth smoking has likely been attenuated by the sale and marketing of mentholated cigarettes, including emerging varieties of established youth brands. This study should inform the Food and Drug Administration regarding the potential public health impact of a menthol ban.